QTL Analyses in Multiple Populations Employed for the Fine Mapping and Identification of Candidate Genes at a Locus Affecting Sugar Accumulation in Melon (Cucumis melo L.) - Argyris, Jason M.; Díaz, Aurora; Ruggieri, Valentino; Fernández, Marta; Jahrmann, Torben; Gibon, Yves; Picó, Belén; Martín-Hernández, Ana M.; Monforte, Antonio J.; Garcia-Mas, Jordi (Frontiers in Plant Science, 2017)
Sugar content is the major determinant of both fruit quality and consumer acceptance in melon (Cucumis melo L), and is a primary target for crop improvement. Near-isogenic lines (NILs) derived from the intraspecific cross between a ‘Piel de Sapo’ (PS) type and the exotic cultivar ‘Songwhan Charmi’ (SC), and several populations generated from the cross of PS x Ames 24294 (“Trigonus”), a wild melon, were used to identify QTL related to sugar and organic acid composition. Seventy-eight QTL were detected across several locations and different years, with three important clusters related to sugar content located on chromosomes 4, 5 and 7. Two PS x SC NILs (SC5-1 and SC5-2) sharing a common genomic interval of 1.7 Mb at the top of chromosome 5 contained QTL reducing soluble solids content and sucrose content by an average of 29 and 68%, respectively. This cluster collocated with QTL affecting sugar content identified in other studies in lines developed from the PS x SC cross and supported the presence of a stable consensus locus involved in sugar accumulation that we named SUCQSC5.1. QTL reducing soluble solids and sucrose content identified in the “Trigonus” mapping populations, as well as QTL identified in previous studies from other ssp. agrestis sources, collocated with SUCQSC5.1, suggesting that they may be allelic and implying a role in domestication. In subNILs derived from the PS x SC5-1 cross, SUCQSC5.1 reduced soluble solids content and sucrose content by an average of 18 and 34%, respectively, and was fine-mapped to a 56.1 kb interval containing four genes. Expression analysis of the candidate genes in mature fruit showed differences between the subNILs with PS alleles that were ‘high’ sugar and SC alleles of ‘low’ sugar phenotypes for MELO3C014519, encoding a putative BEL1-like homeodomain protein. Sequence differences in the gene predicted to affect protein function were restricted to SC and other ssp. agrestis cultivar groups. These results provide the basis for further investigation of genes affecting sugar accumulation in melon.